Efektivitas Manajemen Keuangan Sekolah pada SMK Swasta Lamaholot Larantuka Kabupaten Flores Timur - Karolus Belmo (Jurnal Riset dan Inovasi Manajemen, 2023)
Lamaholot Larantuka Private Vocational School is an educational unit located in Lewoloba Village, Ile Mandiri District, East Flores Regency. As an Educational Institution, every activity carried out at the Lamaholot Private Vocational School is directed to achieve the school's vision and mission. To achieve the vision and mission, Lamaholot Larantuka Private Vocational School must pay attention to the elements of education management, namely curriculum management, student management, facilities and infrastructure management, public relations management, personnel management, and financial management. From the results of the initial research on the management elements above, it was found that phenomena/problems related to financial management had not been managed effectively. This was reinforced in the 2020 and 2021 School Activity and Budget Plans (RKAS), where it was found that several activity plans could not work because there was no reconciliation between targets and budget realization. The research objective to be achieved is that the researcher wants to know and explain the financial management of the Lamaholot Private Vocational School Larantuka based on the principle of the effectiveness of school financial management. In this study, the data collection techniques used were observation, interviews and document studies. While the data analysis technique used to find out and explain the problems at the research location is descriptive qualitative with a school financial management approach which includes (a) school financial management planning at SMKs; (b) implementation of school financial management at SMK; (c) evaluation and accountability of school financial management; and (d) analysis of the effectiveness of school financial management in SMK. From the results of the study it was found that the effectiveness of school financial management at the Lamaholot Larantuka Private Vocational School in 2020 was in the range of 99.52%. It means effective. Meanwhile, the effectiveness of school financial management at the Lamaholot Larantuka Private Vocational School in 2021 is in the range of 99.29% and is said to be effective. Based on the results of this study, the researchers concluded that the effectiveness level of financial management at the Lamaholot Larantuka Private Vocational School for the 2020 and 2021 fiscal years has reached the effective category because it is in the 90% - 100% category.